FORMULASI PEMISAHAN LEMBAGA PEMASYARAKATAN DARI KEMENTERIAN HUKUM DAN HAM UNTUK MEWUJUDKAN KEMANFAATAN HUKUM DALAM TATA KELOLA LEMBAGA PEMERINTAHAN - Hamdan, Riko (Jurnal Hukum dan Keadilan, 2023)
As a state of law, Indonesia must fulfill the concept that this country is a state of law based on constitutional, adheres to the principles of democracy, and recognizes and protects human rights with impartial and free justice. This means that society must carry out government functions based on the Law that has been stipulated in the 1945 Constitution. The approach used in this research is normative juridical. The normative juridical approach is an approach based on primary legal materials by examining theories, concepts, legal principles and laws and regulations related to this research. This research is conducted by conducting a literature review or secondary data through the review of primary, secondary, tertiary legal materials in the form of documents and applicable laws and regulations.The formulation of the separation of the Correctional Institution from the Ministry of Law and Human Rights is needed as an effort to improve the effectiveness of guidance and consideration of executions sentenced to prisoners. The Correctional Institution has the authority over decisions related to sentences imposed on prisoners. Because, the decision of the release letter must be based on the approval of Kalpas until the death sentence can be evaluated if there is a letter of good behavior recommended by the prison.